Weihnachtsausstellung. : 1992. - Kunsthalle Bern, Bern (Bern : Kunsthalle Bern, 1992)
Althaus, Andreas ; Baumann, Marianne ; Baxter, Geoffrey ; Beer, Simon ; Berger, Ueli ; Beyeler, Martin ; Brand, Heinz ; Brignoni, Serge ; Distel, Herbert ; Ebinger, Moritz ; Feller, Beat ; Franticek ; Frentzel, Gunter ; Gärstke, Beate ; Goulart, Vera ; Grunder, Mariann ; Gysin, Béatrice ; Haag, Filip ; Hensler, Markus ; Hilty, Burkhard ; Hostettler, Thomas ; Indermühle, Christian ; Jordi, Ernst ; Jucker, Balthasar ; etc.
Weihnachtsausstellung, Kunsthalle Bern, 12.12.1992 - 7.1.1993
boek